1980
DOI: 10.1152/ajpgi.1980.239.3.g215
|View full text |Cite
|
Sign up to set email alerts
|

Motilin-independent ectopic fronts of the interdigestive myoelectric complex in dogs

Abstract: We have studied in four conscious dogs the relationship between circulating concentrations of motilin and the activity front (phase III) of the interdigestive myoelectric complex. During fasting, cyclic peaks of motilin secretion were concomitant in every instance with the initiation of activity fronts that began in the stomach or duodenum. When somatostatin was administered at doses of 5, 2.5, or 0.625 microgram x kg-1 x h-1 for 3 h, motilin concentrations were stabilized at lowered levels and no activity fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…[33][34][35][36] In our results, the administration of Daikenchu-to with pirenzepine pretreatment significantly increased plasma somatostatin-IS levels compared with Daikenchu-to alone or placebo, while transient elevations in plasma gastrin-IS were inhibited. Sue et al reported that pirenzepine acts on somatostatin cells (D cells) to promote somatostatin release, thereby indirectly suppressing gastrin release from G cells in the stomach.…”
Section: Discussionsupporting
confidence: 54%
“…[33][34][35][36] In our results, the administration of Daikenchu-to with pirenzepine pretreatment significantly increased plasma somatostatin-IS levels compared with Daikenchu-to alone or placebo, while transient elevations in plasma gastrin-IS were inhibited. Sue et al reported that pirenzepine acts on somatostatin cells (D cells) to promote somatostatin release, thereby indirectly suppressing gastrin release from G cells in the stomach.…”
Section: Discussionsupporting
confidence: 54%
“…7,8) In the stomach, somatostatin induces phase-3 activities in the interdigestive state, whereas it inhibits motilin-induced gastrointestinal MMC in the digestive state. 23) In the intestine, somatostatin stimulates peristalsis. 8) In the peristaltic reflex, somatostatin caused descending caudad relaxation via VIP and g-aminobutyric acid release.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin participates in regulating gastrointestinal motility with motilin. [9][10][11][12][13][14] Somatostatin is the first of the gut regulatory peptides (to stimulate MMC-like activity) to have significant therapeutic use of its analogue. 28) Increases in somatostatin might correspond with gastrointestinal motor regulation including the acceleration of gastric emptying by this medicine.…”
Section: Resultsmentioning
confidence: 99%
“…It participates in regulating gastrointestinal motility with motilin. [9][10][11][12][13][14] Motilin has powerful fundic pouch motor-stimulating activity, 15) and is one of the most important factors controlling the regular occurrence of phase-3 contractions of the migrating motor complex (MMC). 16,17) Gastrin stimulates acid secretion and gastrin release is mediated by various mechanisms.…”
mentioning
confidence: 99%